2005
DOI: 10.1002/pssb.200562422
|View full text |Cite
|
Sign up to set email alerts
|

Changes in magnetic and magnetoresistive characteristics of Ni–Fe/Au/Co/Au multilayers induced by annealing

Abstract: PACS 75.47. De, 75.70.Cn In this contribution the influence of annealing on magnetization reversal and on the giant magnetoresistance effect of [Ni 80 Fe 20 /Au(t Au )/Co(t Co )/Au(t Au )] 10 multilayers with t Co = 0.6, 0.8 nm and t Au = 1.5, 2.2 nm was studied. Measurements performed for as-deposited samples and after subsequent annealing at T a (423 K < T a < 523 K) show that the GMR effect is stable under annealing below 475 K. It even slightly increases, for T a above 450 K, opening a path for a GMR va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…As was already shown [3] the MR amplitude in NiFe/Au/ Co/Au MLs is not changed by annealings at T A ≤ 250 • C. Annealings at higher temperatures (T A = 300 • C) lead to a strong degradation of the MR effect (Fig. 1).…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…As was already shown [3] the MR amplitude in NiFe/Au/ Co/Au MLs is not changed by annealings at T A ≤ 250 • C. Annealings at higher temperatures (T A = 300 • C) lead to a strong degradation of the MR effect (Fig. 1).…”
Section: Resultsmentioning
confidence: 51%
“…In particular, it was demonstrated that [NiFe/Au/Co/Au] N multilayers display giant magnetoresistance (GMR) [1] and that their magnetic and magnetoresistive properties can be modified in a broad range by adjusting layers thicknesses [1] and/or using composite magnetic layers [2]. It was also shown that they are resistant to low temperature annealings [3] and display satisfactory temperature stability [4]. The aim of this study is to explain the observed changes of magnetic properties of [NiFe/Au/Co/Au] 10 MLs under the influence of high temperature annealings and to determine Co thickness range assuring the high thermal stability.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For the field applied perpendicularly this leads to the GMR-like resistance changes caused by a creation and an annihilation of domains (see the left inset of Fig. 2b) [12]. It is important to note that the character of the R(H) dependences underwent dramatic changes (GMR amplitude changes are irrelevant to our argumentation).…”
Section: Resultsmentioning
confidence: 88%
“…It is important to note that the character of the R(H) dependences underwent dramatic changes (GMR amplitude changes are irrelevant to our argumentation). Concentrating on the perpendicular configuration, it can be seen that R(H) dependence characteristic of layers with perpendicular anisotropy and the dense domain structure is transformed into the dependence observed for MLs with alternating in-plane and out-of-plane anisotropies in successive layers [12][13][14]. Summing up, the resistance measurements confirm the observation inferred from the M (H) measurements, namely that the IB led to the switching of the EA direction in the 1 nm thick Co layers (see Fig.…”
Section: Resultsmentioning
confidence: 99%